PENYULUHAN DAN PELATIHAN PEMANFAATAN PEKARANGAN SEBAGAI APOTIK HIDUP DAN WARUNG HIDUP DALAM UPAYA MENINGKATKAN KESEJAHTERAAN KAMPUNG YABEMA DISTRIK ELELIM KABUPATEN YALIMO PAPUA - Basa T. Rumahorbo; Rosye H.R. Tanjung (JURNAL PENGABDIAN PAPUA, 2020)
Training activities of plant cultivation as a living pharmacy  in an effort to improve the family welfare in the Yabema village of district Elelim was held on 16 and 22 September 2019. This activity is to answer one of the problems of the limited cultivation in the land owned by the urban Community at Elelim District in terms to improve the family welfare. The method used in this activity is in the form of training by providing material and practice (demonstration) in the target society that is urban society with limited land and yard. This activity involved 24 people from various circles such as youth, students and women and men. From this training activity, the community has been aware of the techniques of verticulture cultivation in optimizing land Utilization. The results of these activities are expected to be further developed to address challenges in order to increase family needs and to improve the welfare of the family itself. Moreover, this activity is also one of the efforts to answer the challenge of mitigation issues against global warming by increasing the number of vegetation which can utilize carbon dioxide in the air. Keywords: cultivation technique, verticulture,the yard, family welfare